2007
DOI: 10.1128/iai.01351-06
|View full text |Cite
|
Sign up to set email alerts
|

Cell Wall Targeting of Laccase of Cryptococcus neoformans during Infection of Mice

Abstract: Laccase is a major virulence factor of the pathogenic fungus Cryptococcus neoformans, which afflicts both immunocompetent and immunocompromised individuals. In the present study, laccase was expressed in C. neoformans lac1⌬ cells as a fusion protein with an N-terminal green fluorescent protein (GFP) using C. neoformans codon usage. The fusion protein was robustly localized to the cell wall at physiological pH, but it was mislocalized at low pH. Structural analysis of the laccase identified a C-terminal region … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
57
0
2

Year Published

2007
2007
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(64 citation statements)
references
References 40 publications
(49 reference statements)
5
57
0
2
Order By: Relevance
“…The early observations, using melanin-lacking mutants isolated by UV irradiation, suggesting the importance of melanin as a virulence factor (Kwon- Chung et al 1982c;Rhodes et al 1982) was confirmed by the use of LAC1 gene-deletion mutants (Salas et al 1996). C. neoformans contains two laccase genes, LAC1 and LAC2, in the genome but only LAC1 is expressed significantly under most conditions and virulence is reduced only when the LAC1 gene is deleted (Zhu and Williamson 2004;Pukkila-Worley et al 2005).The cryptococcal laccase, a member of the multicopper oxidases is localized in the cell walls (Zhu et al 2001;Waterman et al 2007b) and its transport to the cell wall is Sec6 dependent (Panepinto et al 2009). Melanization of cryptococci require numerous additional genes such as the copper transporter Ccc2, the copper chaperone Atx1, the chitin synthase Chs3, the transcriptional coactivator Mbf1, the chromatin remodeling enzyme Snf5 (Walton et al 2005), the transcription factor Rim101, and its regulatory gene Rim20 (Liu et al 2008).…”
Section: Melanin Formationmentioning
confidence: 96%
“…The early observations, using melanin-lacking mutants isolated by UV irradiation, suggesting the importance of melanin as a virulence factor (Kwon- Chung et al 1982c;Rhodes et al 1982) was confirmed by the use of LAC1 gene-deletion mutants (Salas et al 1996). C. neoformans contains two laccase genes, LAC1 and LAC2, in the genome but only LAC1 is expressed significantly under most conditions and virulence is reduced only when the LAC1 gene is deleted (Zhu and Williamson 2004;Pukkila-Worley et al 2005).The cryptococcal laccase, a member of the multicopper oxidases is localized in the cell walls (Zhu et al 2001;Waterman et al 2007b) and its transport to the cell wall is Sec6 dependent (Panepinto et al 2009). Melanization of cryptococci require numerous additional genes such as the copper transporter Ccc2, the copper chaperone Atx1, the chitin synthase Chs3, the transcriptional coactivator Mbf1, the chromatin remodeling enzyme Snf5 (Walton et al 2005), the transcription factor Rim101, and its regulatory gene Rim20 (Liu et al 2008).…”
Section: Melanin Formationmentioning
confidence: 96%
“…Similarly, loss of Vps23 may interrupt the processing and/or transport of laccase (resulting in reduced melanization). Laccase must be loaded with copper during transit through the ER-Golgi compartment network, and it must be properly localized in the cell wall (68). Capsule polysaccharide is also found in extracellular vesicles, although the extent of the contribution of the latter vesicles to capsule formation is not yet clear (67).…”
Section: Discussionmentioning
confidence: 99%
“…LAC1 mRNA transcription is active in cerebrospinal fluid of C. neoformans-infected rabbits and is an important virulence factor in in vivo models for cryptococcosis (72). Moreover, during brain infection, there is a strong localization of a Lac1-GFP fusion protein at the cryptococcal cell wall, as opposed to the lungs where this enzyme is localized in the cytosol, suggesting a predominant role of the enzyme during the brain infection (73). Several other C. neoformans proteins are also required for melanin biogenesis, such as the Ccc2 Cu ϩ pump that facilitates Cu metallation in the secretory compartment and is known to be a virulence factor in murine infection models (33).…”
Section: Laccases and The Melanin Biosynthetic Pathwaymentioning
confidence: 99%